Experimental and theoretical investigations of unbalance flexible rotor in active magnetic bearings considering backup bearings contacts. (April 2022) - Ebrahimi, Reza
This paper describes the experimental verification of an unbalance flexible rotor model in active magnetic bearings. The dynamic modeling takes into account the gyroscopic moments of the disk, geometric coupling of the magnetic actuators, and contact forces of the backup bearings. The Rung–Kutta method is used to integrate the equations of motion. The nonlinear dynamic response is analyzed using bifurcation plots, disc center trajectories, Fast Fourier Transforms, Poincaré maps, and maximum Lyapunov exponent. The analysis is carried out for different values of rotating speed and unbalance eccentricity. In the unbalance test, a concentrated mass of 5 gr is attached in three radial position of the disk. The numerical simulations and experiments prove that a variety of nonlinear dynamical phenomena such as period -3, -4, -8, periodic, quasi-periodic, and chaotic motions occur in the system. The results indicate that the response of the rotor returns back to a regular motion by increasing the rotational speed. Also, by increasing the unbalance eccentricity, the first irregular motion initiates at much higher rotational speeds. Therefore, sufficient attention should be paid to these factors in design of a flexible rotor system equipped with both active magnetic bearings and backup bearings in order to ensure system reliability.